PREVENTION OF ERRORS AND COMPLICATIONS AT THE STAGES OF ENDODONTIC TREATMENT (American Journal of Pedagogical and Educational Research, 2025)
The article examines the main errors and complications that occur at different stages of endodontic treatment, as well as methods for their prevention. The relevance of the study is due to the high prevalence of endodontic interventions and a significant frequency of failures associated with anatomical features of the root canals, technical errors, and insufficient adherence to clinical protocols. The purpose of the study was to analyze the causes of endodontic errors and to develop preventive measures aimed at improving the effectiveness and safety of treatment. The work used clinical observation data, results of radiological and instrumental diagnostic methods, as well as analysis of modern scientific sources.